Judging Value in a Time of Information Cacophony: Young Adults, Social media, and the Messiness of do-it-Yourself Expertise. (July 2022) - Cotter, Kelley; Thorson, Kjerstin
In this paper, we explore U.S. young adults' strategies for evaluating news and information value within the rapidly changing, increasingly digitalized media environment. We draw on interviews with U.S. young adults conducted between April and November 2020. Based on our findings, we develop the concept of information cacophony to characterize young adults' experience of the contemporary information environment. Information cacophony is characterized by the jarring noise of many, discordant voices offering up information, under conditions of low media trust and an absence of a pre-defined epistemic hierarchy of sources. We illustrate how the volume and discordance of voices circulating content online makes it difficult for young adults to know what to believe, and show that young peoples' strategies for evaluating information are deeply entangled with the sociality and emotionality of the experience of information cacophony. We argue that existing theory is not yet well-developed to account for content evaluations and effects resulting from the novel complexities of navigating information cacophony. Existing work remains focused primarily on news exposure and effects, which misses the broader informational context within which young adults find themselves, and evolving strategies for evaluating information.